2015
DOI: 10.1002/hed.24159
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio and overall survival in all sites of head and neck squamous cell carcinoma

Abstract: Background Current prognostic criteria are insufficient in predicting outcomes in head and neck cancers, necessitating new, readily available biomarkers Methods Pretreatment neutrophil and lymphocyte counts and their ratio (NLR) were retrospectively investigated for correlation with overall survival while controlling for demographic and clinical confounders. Results Patients in the highest tertile of neutrophil counts and those in the lowest tertile of lymphocytes experienced shorter survival than the rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
158
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(190 citation statements)
references
References 38 publications
15
158
3
2
Order By: Relevance
“…14 None of the other studies accounted for HPV status, with the exception of Rachidi et al, 10 who analyzed several aspects of the relationship between HPV status and the NLR. Other prior studies in HNSCC focused on oral cancer, and our cohort did not contain any oral cavity cancers, so it is difficult to compare these studies as the biology of oral cavity cancers and oropharyngeal/laryngeal cancers may not be comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 None of the other studies accounted for HPV status, with the exception of Rachidi et al, 10 who analyzed several aspects of the relationship between HPV status and the NLR. Other prior studies in HNSCC focused on oral cancer, and our cohort did not contain any oral cavity cancers, so it is difficult to compare these studies as the biology of oral cavity cancers and oropharyngeal/laryngeal cancers may not be comparable.…”
Section: Discussionmentioning
confidence: 99%
“…2 A high NLR has also been associated with a poor prognosis for a variety of other cancers, including hepatocellular carcinoma, 3 pancreatic cancer, 4 urinary cancer, 5 and biliary tract cancer. Rassouli et al 9 have shown that PLR is a predictor of mortality and NLR is a predictor of recurrence, whereas Rachidi et al 10 8 However, only a few studies have examined the prognostic value of these inflammatory markers in head and neck squamous cell carcinoma (HNSCC).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the relationship between inflammatory response and tumor development, researchers have recently introduced the use of inflammation-based prognostic scores, as determined by means of general serological indicators such as neutrophils, lymphocytes, CRP, and alb363738. The initial study related to the CRP/alb ratio involved a patient with a severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…Rachidi et al (13) also reported different results in their work on head and neck squamous cell carcinoma (HNSCC). They found that NLR was associated with worse prognosis in HNSCC patients.…”
Section: Discussion:-mentioning
confidence: 99%